How democracy promoters respond to global autocratisation - Sonja Grimm; Brigitte Weiffen; Karina Mross (German Institute of Development and Sustainability (IDOS), 2025)
Autocratisation has become a defining global trend, replacing decades of democratisation and forcing democracy promoters to rethink their approaches. Democracy promoters must adapt to several challenges, including autocratisation in target countries, the rise of powerful autocratic competitors in the global arena, and challenges to democracy in some of the very countries promoting it. Moreover, the crisis in development aid fuelled by the withdrawal of funding by the United States (US) and other countries, and their prioritisation of security, pose further structural challenges. This Policy Brief examines the effects of the global trend of autocratisation on international democracy promotion, summarising findings from a collaborative research project (Grimm et al., 2025). The findings show that democracy promoters respond to these shifts in four ways: 1) choosing to "carry on and observe" by continuing existing programmes and maintaining cooperation rather than risking confrontation; 2) reinforcing rhetorical and diplomatic efforts for democracy, to signal continued commitment; 3) selectively adapting policies and strategies, with renewed focus on civil society, education and targeted funding, yet rarely making substantive policy changes; 4) disengaging by shifting cooperation toward less politicised fields or withdrawing entirely. So far, however, we lack evidence on the effectiveness of these responses to counter autocratisation. Given the new challenges to democracy promotion arising from the changed international context, democracy promoters should consider taking the following actions: Ramping up efforts to counter the rise of autocratic powers: Democracy promoters should proactively deepen their pro-democracy cooperation, reaffirm democratic alliances and maintain a clear normative profile. They should invest in long-term partnerships with governments and civil societies committed to democratic reform. Revitalising the norm of democracy: Democracy promoters must make a case for why democracy matters, highlighting that it delivers rights and freedoms, as well as stability, prosperity, and peace - at least as effectively as autocratic regimes. Emphasising its tangible benefits can help restore faith in its long-term value, and counter the appeal of autocratic alternatives. Coordinating strategies and combining strengths: Joint frameworks for action among democracy promoters are needed that allow for the simultaneous use of different instruments, e.g. political dialogue, development cooperation, human rights advocacy and economic incentives. Combining direct and indirect democracy promotion increases adaptability. Adapting democracy promotion to the context: In contexts where democracy is being eroded, prioritise the defence of current democratic institutions, actors and practices rather than pushing for rapid reforms. Strengthen local actors who uphold democratic values, protect them against repression and maintain spaces for civic participation. Restoring credibility: Democracy-promoting states and organisations should openly discuss challenges to democracy at home in order to rebuild trust, strengthen legitimacy and facilitate collaboration in defence of democracy. Reinforcing own democratic institutions and upholding the rule of law contributes to restoring the credibility of democracy promoters.
Keywords: 320; democracy; autocracy